2020
DOI: 10.1093/eurjpc/zwaa047
|View full text |Cite
|
Sign up to set email alerts
|

EU-Wide Cross-Sectional Observational Study of Lipid-Modifying Therapy Use in Secondary and Primary Care: the DA VINCI study

Abstract: Aims To provide contemporary data on the implementation of European guideline recommendations for lipid-lowering therapies (LLTs) across different settings and populations and how this impacts low-density lipoprotein cholesterol (LDL-C) goal achievement. Methods and results An 18 country, cross-sectional, observational study of patients prescribed LLT for primary or secondary prevention in primary or secondary care across Eur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

29
342
0
39

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 496 publications
(410 citation statements)
references
References 9 publications
29
342
0
39
Order By: Relevance
“…Use of additional and effective add-on treatments in patients for whom statins alone do not sufficiently lower LDL-C levels, or alternative treatments for patients who cannot take statins, may help to reduce the risk of ASCVD. Despite this, a recent cross-sectional study of almost 6000 patients in 18 countries in the European Union found that combination of a statin with another lipid-lowering agent was low, including those patients who are at high and very high risk for ASCVD [6]. To date, add-on or alternative treatments to statins include primarily ezetimibe, PCSK9 inhibitors, and/or bile acid sequestrants, mainly because they have been proven to reduce LDL-C levels and cardiovascular events in randomized, placebo-controlled trials [7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…Use of additional and effective add-on treatments in patients for whom statins alone do not sufficiently lower LDL-C levels, or alternative treatments for patients who cannot take statins, may help to reduce the risk of ASCVD. Despite this, a recent cross-sectional study of almost 6000 patients in 18 countries in the European Union found that combination of a statin with another lipid-lowering agent was low, including those patients who are at high and very high risk for ASCVD [6]. To date, add-on or alternative treatments to statins include primarily ezetimibe, PCSK9 inhibitors, and/or bile acid sequestrants, mainly because they have been proven to reduce LDL-C levels and cardiovascular events in randomized, placebo-controlled trials [7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…Despite this, there is a considerable shortfall with what is put into action. Real-world data show that poor LDL-C goal attainment is an issue across all categories of high-risk and very-high-risk patients [5,6]. Limited uptake of high-intensity statin therapy [6][7][8][9][10], and underuse of ezetimibe contribute [6,11].…”
Section: Introductionmentioning
confidence: 99%
“…Real-world data show that poor LDL-C goal attainment is an issue across all categories of high-risk and very-high-risk patients [5,6]. Limited uptake of high-intensity statin therapy [6][7][8][9][10], and underuse of ezetimibe contribute [6,11]. Suboptimal treatment adherence is a major issue, due to various reasons including adverse effects (whether perceived or real), and clinician inertia [9,12,13] This EAS Task Force recognizes that the new LDL-C goals for high and very-high-risk patients with dyslipidaemia are even more demanding than previously; indeed, in real-world practice only about one-third attain LDL-C goal [6].…”
Section: Introductionmentioning
confidence: 99%
“…The EUROASPIRE IV [19] reported an achievement rate of 19.5%, which climbed to 29% in EUROASPIRE V [31]. The latest LLT dedicated study -the DA VINCI study [32]-in 18 European countries demonstrated 2016 ESC/EAS goal attainment rate of 39%, even greater than the abovementioned registries. However, the gaps between clinical guidelines and clinical practice for dyslipidemia management persist and will be further exacerbated by the stricter 2019 ESC/EAS guidelines.…”
Section: Discussionmentioning
confidence: 95%
“…Concerning LLT, the EUROASPIRE IV [19], V [31], and DA VINCI [32] studies demonstrated a signi cant down-titration of statin's intensity over the rst year after the index event resulting in less than half of the patients treated with high-intensity statins at one year. The same downward trend in high-intensity utilization was also observed in IDEAL-LDL (high-intensity statin: 84.4% at discharge vs. 72.4% at 1-year).…”
Section: Discussionmentioning
confidence: 99%